PENERAPAN AUDIO DESCRIPTION PADA KARYA DOKUMENTER PENDEK SEJAUH MATA MEMANDANG - Sukron Madani Dwi Prasetyo; I Nyoman Payuyasa; I Nyoman Suardina (CALACCITRA: JURNAL FILM DAN TELEVISI, 2023)
The production of the short documentary film “Sejauh Mata Memandang” was created to be able to motivate people with disabilities, especially the blind and deaf people to be able to provide space and access so they can enjoy films in general. This production will also be equipped with an audio description as a feature that helps people with disabilities to enjoy the film along with the message contained in it. The production of this work is based on the results of research and the issue of disability discrimination in Bali. The blind are equal and have the right to live side by side with the general public. Blinds have the right to love one another without discrimination. The research was carried out using an observational approach to blind persons with disabilities. The method used is in the form of quantitative and qualitative with blended learning to be able to create optional issues that can be used for the creation of documentary short films. The results of the research conducted show that the blind do not have access to the convenience of watching movies. People with disabilities need help from other parties or use audio descriptions in enjoying film. This work endeavored to have a broad impact on blind and deaf friends and to be able to raise awareness for every filmmaker to start taking into account the audio description feature facility in every film work creates.